2005
DOI: 10.1111/j.1741-4520.2005.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic investigation of the lectin method for separation and recovery of nucleated red blood cells in maternal blood, and a study into the frequency of nucleated red blood cells in fetomaternal disorders

Abstract: We previously reported the separation and recovery of nucleated red blood cells (NRBCs) in maternal blood using the lectin method. In the present study, we verified the lectin method and investigated the appearance of NRBCs during pregnancy. For the concentration of lectin soy bean agglutinin, 7 mL of maternal peripheral blood was collected from 20 subjects, and the relative fluorescence intensity was measured using flowcytometry; 50 mg/mL, used in previous studies, was the optimal concentration. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(27 reference statements)
1
0
0
Order By: Relevance
“…Several groups have reported that conditions such as placenta previa, pre‐eclampsia, intrauterine growth restriction, pregnancy‐induced hypertension, diabetes mellitus, trisomy 18, and trisomy 21 are associated with increased transfer of fetal erythroblasts into the maternal circulation. Our findings also suggest that imminent abortion may enhance fetomaternal cellular trafficking.…”
Section: Discussionsupporting
confidence: 60%
“…Several groups have reported that conditions such as placenta previa, pre‐eclampsia, intrauterine growth restriction, pregnancy‐induced hypertension, diabetes mellitus, trisomy 18, and trisomy 21 are associated with increased transfer of fetal erythroblasts into the maternal circulation. Our findings also suggest that imminent abortion may enhance fetomaternal cellular trafficking.…”
Section: Discussionsupporting
confidence: 60%